Plant indicator species for the conservation of priority forest in an insular forestry area, Yambaru, Okinawa Island. Issue 3 (4th May 2021) - Abe, Tetsuto; Kudo, Takami; Saito, Kazuhiko; Takashima, Atsushi; Miyamoto, Asako
ABSTRACT: Degradation of old-growth forests is an important issue for global biodiversity conservation. Robust indicator species greatly facilitate the identification of old-growth forests requiring protection. Understanding why particular species are associated with priority forests is necessary for assessing the reliability of indicator species. Here, we surveyed the vegetation of 69 sites in Yambaru forests (Okinawa Island) varying in forest age and analyzed the relationships between the dominance of vascular species and three criterion parameters (forest age and species richness (SR) of epiphytes and endangered plants). Eleven species showing significant positive correlations with three parameters were designated as potential candidate indicator species, ten of which were woody species. Of the above eleven candidate indicator species, Distylium racemosum was considered one of the most useful indicator species because it can be easily identified in the field and its ecological characteristics are well documented. Regarding three woody traits – sprouting ability, annual growth rate and wood density – which are expected as the cause of indexing, endangered SR increased when tree species with low sprouting ability and high wood density were dominant, and epiphyte SR increased when tree species with low annual growth rate and high wood density were dominant. These woody species traits were associated with forest age and could explain why D. racemosum is an indicator of priority forest. These results suggest that large trees with such woody characteristics are effective indicators of priority forests.